Building social cohesion in ethnically mixed schools - Alan, Sule,Baysan, Ceren,Gumren, Mert,Kubilay, Elif (CESifo, Center for Economic Studies & Ifo Institute, 2020)
We evaluate the impact of an educational program that aims to build social cohesion in ethnically mixed schools by developing perspective-taking ability in children. The program is implemented in a high-stakes context where the ethnic composition in schools has changed due to a massive influx of refugee children. We measure a comprehensive set of outcomes that characterize a cohesive school environment, including peer violence incidents, the prevalence of inter-ethnic social ties, and prosocial behavior. Using randomized variation in program implementation, we find that the program significantly lowers peer violence and victimization on school grounds. The program also reduces the likelihood of social exclusion and increases inter-ethnic social ties in the classroom. We find that the program significantly improves prosocial behavior, measured by incentivized tasks: treated students exhibit significantly higher trust, reciprocity, and altruism toward each other as well as toward anonymous out-school peers. We show that this enhanced prosociality is welfare improving from the ex-post payoff perspective. We investigate multiple channels that could explain the results, including ethnic bias, impulsivity, empathetic concern, behavioral norms, and perspective-taking. Children’s increased effort to take others’ perspectives emerges as the most robust mechanism to explain our results.
10419/229572
Keywords: Graue Literatur; social cohesion; social exclusion; ethnic segregation; perspective taking